Cadmium resistance from Staphylococcus aureus plasmid pI258 cadA gene results from a cadmium-efflux ATPase. - Nucifora, G (1989)
Cadmium resistance specified by the cadA determinant of Staphylococcus aureus plasmid pI258 results from the functioning of a cadmium-efflux system. In the nucleotide sequence of the DNA fragment containing the cadA determinant, two open reading frames were identified. The larger one, corresponding to a predicted polypeptide of 727 amino acid residues, is necessary and sufficient for expression of cadmium resistance. Comparison of the CadA amino acid sequence with known protein sequences suggested that CadA is a member of the E1E2 cation-translocating ATPases, similar to the K+-uptake ATPases of Gram-positive and Gram-negative bacteria. The sequence homology is lower but significant with other E1E2-type ATPases, including the H+-efflux ATPases of eukaryotic microbes and the Ca2+- and Na+/K+-ATPases of animals. A frame-shift mutation in the middle of the gene destroys the Cd2+-resistance phenotype. A detailed model for the putative CadA ATPase based on homologies to other E1E2 ATPases is presented and discussed.